Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Usahatani Jagung Di Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Novita Sari Matondang; Siska Yulianita Lubis; Fuad Balatif (Public Service and Governance Journal, 2023)
Based on the results of the data analysis conducted, it was found that the variable land area has a significant effect on the income of corn farmers because the wider the land owned will increase the income of farmers because the more land planted is also encouraged by other factors such as plant care. The variable cost of fertilizer has no significant effect on the income of corn farming because the use of fertilizer must be in accordance with the recommended dosage. If it exceeds it can cause plant death and continuous application of fertilizers can have a bad effect on soil conditions. Soil becomes quickly hardened, less able to store water. The cost of pesticides has no significant effect on the income of corn farming because the excessive use of pesticides is not friendly to the environment and the health of farmers, because nutrients in the soil are eroded in the long term and productivity decreases. Seed costs do not have a significant effect on corn farming income. That is, the more seeds used, the greater the production yields, but there is still a maximum limit for this use, if it is used beyond this limit it will reduce production yields. The variable amount of labor does not have a significant effect on the income of farmers because the more labor used will reduce income to provide wages, the labor used in this case is daily workers and only at harvest time. The output price variable does not have a significant effect on farmer income where the increase or a decrease in the total output price will result in an increase and decrease in corn income in the Waterfall Village, Pantai Cermin District.